2020
DOI: 10.1111/jdi.13393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenosine monophosphate‐activated protein kinase–p53–Krüppel‐like factor 2a pathway in hyperglycemia‐induced cardiac remodeling in adult zebrafish

Abstract: Aims/Introduction Diabetic cardiomyopathy is a type of myocardial disease. It causes left ventricular hypertrophy, followed by diastolic and systolic dysfunction, eventually leading to congestive heart failure. However, the underlying mechanism still requires further elucidation. Materials and Methods A high‐glucose zebrafish model was constructed by administering streptozocin intraperitoneally to enhance the development of cardiomyopathy and then treated with adenosine monophosphate‐activated protein kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…A hyperglycemia-induced model of diabetic CM in adult zebrafish induces cardiac hypertrophy and impaired diastolic function followed by impaired systolic function ( Sun et al, 2017 ). In another diabetic CM model, hyperglycemia is induced by intraperitoneal streptozocin injections, leading to heart enlargement, arrhythmias, and diastolic dysfunction followed by systolic dysfunction ( Wang et al, 2020 ). These models are relevant for investigating diabetic CM and HF.…”
Section: Other Heart Failure Modelsmentioning
confidence: 99%
“…A hyperglycemia-induced model of diabetic CM in adult zebrafish induces cardiac hypertrophy and impaired diastolic function followed by impaired systolic function ( Sun et al, 2017 ). In another diabetic CM model, hyperglycemia is induced by intraperitoneal streptozocin injections, leading to heart enlargement, arrhythmias, and diastolic dysfunction followed by systolic dysfunction ( Wang et al, 2020 ). These models are relevant for investigating diabetic CM and HF.…”
Section: Other Heart Failure Modelsmentioning
confidence: 99%
“…Zebrafish metabolism research has advanced slowly compared to the cardiovascular discipline due to these and other factors. Table 4 presents some of the established metabolic disorder models: acute hyperglycemia [ 131 , 132 , 133 , 134 ], chronic hyperglycemia [ 133 , 134 , 135 , 136 , 137 , 138 ], genetically induced [ 139 , 140 , 141 ], and obesity [ 142 , 143 , 144 ]. We discuss select zebrafish-based metabolic disease models below.…”
Section: Metabolic Disease Modelsmentioning
confidence: 99%
“…It has been reported that KLF2a exerts cardio-protective effects through the AMPK-p53-KLF2a pathway. In a Streptozocin (STZ)-induced hyperglycemic zebrafish model, Wang et al ( 61 ) found that decreasing phosphorylated AMPK elevated p53, leading to KLF2a downregulation, which in turn, promoted cardiomyocyte apoptosis and induced cardiac remodeling and dysfunction. KLF10 participates in the regulation of various aspects of tissue homeostasis and cellular functions, including proliferation, differentiation, and apoptosis ( 155 , 156 ).…”
Section: Klfs and Cardiomyopathymentioning
confidence: 99%